The Cell A Molecular Approach - Cooper, Geoffrey M. Hausman, Robert E. (ASM Press, 2004)
Because molecular and cellular biology is such an exciting and rapidly moving area of science, teaching it at the undergraduate level is a rewarding, yet challenging, task. This book meets this challenge by providing students with not only the most current information, but also with an introduction to the experimental nature of contemporary research. Designed for use in introductory cell biology courses, it presents current comprehensive science in a readable and cohesive text that students can master in the course of one semester and explores such topics as cell structure and function, developmental biology, the nervous and immune systems, and plant biology. Each chapter includes a section on experimentation and medical applications.